The mediating effects of moral disengagement and aggressive humor style: Dark Triad traits and schadenfreude - Sharafi Zadegan, Milad; Pourhosein, Reza; Azizi, Zohreh (Frontiers in Psychology, 2024)
Background: While schadenfreude is commonly experienced in interpersonal relationships, it is generally considered immoral. Although previous research has explored the factors relating to schadenfreude, including certain personality traits, moral disengagement, and humor styles, our understanding of these factors remains limited. The present study examined the mediating effects of moral disengagement and aggressive humor style in the relationship between the Dark Triad traits and schadenfreude. Methods: In this study, a sample of 693 Iranian students (69.4% female), was recruited using a convenient sampling method, consisting of 330 undergraduate, 230 graduate, and 133 Ph.D. students. The trait schadenfreude scale, the short Dark Triad, the moral disengagement scale, and the aggressive humor style scale were measured through an online survey. Results: The study found that Machiavellianism, narcissism, and psychopathy were positively related to schadenfreude, aggressive humor style, and moral disengagement. Additionally, aggressive humor style and moral disengagement mediated the relationship between Machiavellianism, narcissism, and psychopathy with schadenfreude. Conclusion: This study provides insights into the complex relationships between Dark Triad traits, moral disengagement, aggressive humor style, and schadenfreude. The findings suggest that individuals with higher levels of Dark Triad traits may be more likely to experience pleasure from others' misfortunes. Furthermore, the study highlights the importance of moral disengagement and aggressive humor style as potential mechanisms underlying the relationship between Dark Triad traits and schadenfreude. Further research should be done to explore the motivational factors influencing schadenfreude in specific settings, thereby elucidating these connections.